2013
DOI: 10.1002/bit.24899
|View full text |Cite
|
Sign up to set email alerts
|

Suspension culture of hepatocyte‐derived reporter cells in presence of albumin to form stable three‐dimensional spheroids

Abstract: Several studies in the past have formed 3-dimensional (3D) spheroids of primary hepatocytes in suspension culture. Unfortunately, primary hepatocytes in a suspension environment tend to lose their differentiated function over time, generally due to damage from fluid shear stress and eventual spheroid settling. We have therefore created a novel suspension culture system, by seeding H35 rat hepatoma cells, a hepatocyte-derived cell line, in a 24-well tissue culture polystyrene (TCPS) plate placed atop an orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…They showed that an intact actin network was required for spheroid formation, and particularly, the actin configuration was dependent on the cell–cell interactions with the cells in the center of the spheroids showing cuboidal shape with cortical actin and the cells at the periphery of the spheroids showing spread cells with extended actin filaments . We have observed that the extensive cell–cell interactions in spheroids lead to contact inhibition of cellular proliferation and trigger superior cellular differentiation . Glicklis et al assert that spheroids of 100 µm diameter are ideal for maximizing cell–cell interaction while maintaining adequate oxygen transport to cells located near the spheroid center .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…They showed that an intact actin network was required for spheroid formation, and particularly, the actin configuration was dependent on the cell–cell interactions with the cells in the center of the spheroids showing cuboidal shape with cortical actin and the cells at the periphery of the spheroids showing spread cells with extended actin filaments . We have observed that the extensive cell–cell interactions in spheroids lead to contact inhibition of cellular proliferation and trigger superior cellular differentiation . Glicklis et al assert that spheroids of 100 µm diameter are ideal for maximizing cell–cell interaction while maintaining adequate oxygen transport to cells located near the spheroid center .…”
Section: Resultsmentioning
confidence: 92%
“…Nevertheless, irregularly shaped aggregates have been documented in the past, as when Nelson et al cultured primary porcine hepatocytes in low‐shear microgravity within an NASA bioreactor . During our previous studies, H35 hepatoma cells cultured in suspension also produced very large globular aggregates in the presence of bovine serum albumin dissolved within the culture medium …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor spheroids exhibit many distinct advantages in resembling the 3D cytoarchitecture and pathophysiological micromilieu of tumors [11]. The established 3D hepatocyte cultures in some studies show better cell structure and liver-specific functions [12]. HCC spheroids also exhibit the most malignant properties of HCC tumors [13].…”
Section: Introductionmentioning
confidence: 99%